Prospective investigation of folic acid supplements before and during early pregnancy and paediatric and adult cancers in the Chinese children and families cohort: a pilot study in a sample of rural and urban families. Issue 7 (30th July 2018) - Linet, Martha S; Wang, Linhong; Wang, Ning; Berry, Robert J; Chao, Ann; Hao, Ling; Li, Zhu; Fang, Liwen; Yin, Peng; Potischman, Nancy; Sun, Xin; Meng, Fanweng; et al.
Abstract : Objective: To determine the feasibility of long-term prospective follow-up and ascertainment of cancer in offspring and mothers from the 1993–1995 Chinese Community Intervention Program that provided folic acid supplements before and during early pregnancy to reduce neural tube defects. Design: Feasibility pilot study for a prospective cohort study. Setting: Families residing during 2012–2013 in one rural and one urban county from 21 counties in 3 provinces in China included in the Community Intervention Program campaign. Participants: The feasibility study targeted 560 families, including 280 from the rural and 280 from the urban county included in the large original study; about half of mothers in each group had taken and half had not taken folic acid supplements. Intervention: The planned new study is observational. Primary and secondary outcome measures: Primary: incidence of paediatric cancers in offspring; secondary: other chronic diseases in offspring and chronic diseases in mothers Results: Only 3.4% of pilot study families could not be found, 3.9% had moved out of the study area and 8.8% refused to participate. Interviews were completed by 82% of mothers, 79% of fathers and 83% of offspring in the 560 families. Almost all mothers and offspring who were interviewed also participated in anthropometric measurements. We found notable urban–rural differences in sociodemographic and lifestyle characteristics of the parents, but fewer differences among the offspring. In eight catchment area hospitals, we identified a broad range of paediatric cancers diagnosed during 1994–2013, although paediatric brain tumours, lymphomas and rarer cancers were likely under-represented. Conclusions: Overall, 20 years after the original Community Intervention Program, the pilot study achieved high levels of follow-up and family member interview participation, and identified substantial numbers of paediatric malignancies during 1994–2013 in catchment area hospitals. Next steps and strategies for overcoming limitations are described.